2023
DOI: 10.1002/nano.202300055
|View full text |Cite
|
Sign up to set email alerts
|

The relationship and functional links between human age, growth, and biomedical implants: A review on the application of bulk and nanomaterials

Abstract: Biomaterials are synthetic materials used in making devices for replacing parts of a living being and to function efficiently while interacting with living tissue. Contrary to orthodox medicine in which damaged parts are amputated, the emergence of biomaterials has changed the trend. Different biomaterials including biomedical implants are being developed for different uses within the biomedical field. Thus, biomedical implants are a rapidly advancing class of biomaterials that are currently used for the repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 125 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…This positive trend suggests that the reinforcing effects of Dombeya fibers and paper particles contribute to improved hardness, potentially enhancing the suitability of the composite for applications where resistance to surface penetration is crucial. This finding implies a favorable combination of hardness properties in the biocomposite, which is advantageous for composite development [1]. The effective interfacial adhesion between the fibers/particles and the epoxy matrix, the uniform dispersion of Dombeya fibers within the matrix, and the method of reinforcing the paper particles within the polymer matrix are all responsible for the observed improvement.…”
Section: Hardness Propertymentioning
confidence: 90%
See 2 more Smart Citations
“…This positive trend suggests that the reinforcing effects of Dombeya fibers and paper particles contribute to improved hardness, potentially enhancing the suitability of the composite for applications where resistance to surface penetration is crucial. This finding implies a favorable combination of hardness properties in the biocomposite, which is advantageous for composite development [1]. The effective interfacial adhesion between the fibers/particles and the epoxy matrix, the uniform dispersion of Dombeya fibers within the matrix, and the method of reinforcing the paper particles within the polymer matrix are all responsible for the observed improvement.…”
Section: Hardness Propertymentioning
confidence: 90%
“…Notably, the 3wt% and 6wt% reinforced biocomposites demonstrated superior water resistance properties. Hydrophilic behavior might be caused by insufficient wettability and interfacial adhesion between the fibers/fillers and the polymer matrix, as previous studies have shown [1], [29]. Consequently, Dombeya fiber/paper-particle-hybridreinforced biocomposites could find applications in areas where water resistance is crucial.…”
Section: Fluid Absorption Properties (Water Media)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, part of the reason for low dental implantation demand at this age group can based on the fact that the teeth at this stage are usually temporary, and if removed, the possibility of it been replace naturally with permanent teeth is certain. Also, based on human activities, children are less susceptible to human-induced hazards compared to adolescents and adults [15] . The use of implants in this stage is only in rare cases, especially if the patient has an underlying disease like Leukemia or cancer, which is still a whole controversy in the medical field.…”
Section: Childhoodmentioning
confidence: 99%
“…Recently, different biomaterials, including biomedical implants, are being developed for different uses within the biomedical field. 7 Due to the growing need for biomaterials, researchers are now converting available agricultural wastes to biomaterials in large quantities. 8 The emergence of agro-wastes for the production of hydroxyapatite serves as an alternative inorganic source for bones and tooth replacement due to their similar biomineral constituents.…”
Section: Introductionmentioning
confidence: 99%